The employees’ work ethics influence the organizational performance in hospitality industry / Hafiz Ariffin and Khairul Mohd Billah Awang - Ariffin, Hafiz; Awang, Khairul Mohd Billah (2017)
The purposes of this study are to identify the elements of employees' work ethics in the hospitality industry and to determine the most important element of employees’ work ethics that influence the organizational performance. This research paper is conducted using the argumentative of secondary data. The limitation of the study such as availability of the materials, time and diversions lead us to that research methodology. However, the finding and discussion showed that teamwork is the most influence the organizational performance other than respect, hard work and the centrality of work. The outcome of this study perhaps could help the managers to take look into the things that can really motivate the employees into having a great ethical of work at their workplace. The students who are intent to pursue the career in the hospitality' industry also able to consider the elements discussed as applying it into their work life.